Small-molecule profiling for steroid receptor activity using a universal steroid receptor reporter assay. Issue 217 (March 2022) - Eerlings, Roy; Barbakadze, Nana; Nguyen, Tien; Nadaraia, Nanuli; Smeets, Elien; Moris, Lisa; Handle, Florian; El Kharraz, Sarah; Devlies, Wout; Voet, Arnout; Dehaen, Wim; Claessens, Frank; et al.
Highlights: Combination of response elements for keto-steroid and estrogen receptors. Universal steroid receptor reporter assay profiles small-molecules against all SRs. Steroidal ketones as substrates for triazolization reactions. Abstract: A critical step in the development of novel drug candidates for the treatment of steroid related diseases is ensuring the absence of crosstalk with steroid receptors (SRs). Establishing this SR cross-reactivity profile requires multiple reporter assays as each SR associates with its unique enhancer region, a labor intensive and time-consuming approach. To overcome this need for multi-reporter assays, we established a steroid receptor inducible luciferase reporter assay (SRi-Luc) that allows side-by-side examination of agonistic and antagonistic properties of small-molecules on all steroid receptors. This state-of-the-art SRi-Luc consists of a unique alteration of four distinct keto-steroid- and estrogen response elements. As proof of principle, the SRi-Luc assay was used to profile a set of novel designed steroidal 1, 2, 3-triazoles. These triazolized steroidal compounds were developed via our in-house triazolization methodology, in which an enolizable ketone is converted into a triazolo-fused or -linked analog by treatment with a primary amine or ammonium salt in the presence of 4-nitrophenyl azide. From these designed steroidal 1, 2, 3-triazoles, six successfully reduced androgen receptor activity by 40 %. Although opted as antiandrogens, their cross-reactivity with other SRs was apparent in our SRi-Luc assay and rendered them unsuited for further antagonist development and clinical use. Overall, the SRi-Luc overcomes the need of multi-reporter assays for the profiling of small-molecules on all SRs. This not only reduces the risk of introducing biases, it as well accelerates early-stage drug discovery when designing particular SR selective (ant)agonists or characterizing off-target effects of lead molecules acting on any drug target.